G GAMBARAN MOTIVASI SISWA DALAM PEMBELAJARAN SIMULASI KOMUNIKASI DIGITAL DI MASA PANDEMI COVID 19 KELAS X TKR SMK S8 GRAKARSAA KOTA BENGKULU - resti nopita sari (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
This study aims to determine the description of student's motivation in learning digital commucations during the covid 19 pandemic. this research was conducted on 30 - 30 september 2021 at SMK S8 Grakarsa Bengkulu City, street Adam Malik Km8. the benefits of this research are that it makes students enthusiastic about learning in participating in learning minimizes feclings of boredom, helps student no to give up easily. the approach method used in this study uses descrriptive qualitative methods, whith interviews, and observations and documentation. this researchers at SMK S8 Grakarsa Bengkulu City with the subject of teacher researchers teaching in class X TKR on digital commucation simulation subjectc, the result of this study were obtained through interviews and observations of the results of interviews conducted on Mrs. E. it indicated that the teacher to the students was inaccorgiven by the teacher function as a facilitator an motivator.